Application of Sharia Marketing to the Chip Paste Marketing Strategy: A Case Study in Babadan Village Patianrowo - Adi Putra, Silachi Agusta; Agustina, Maulida (Journal of Sharia Economic Law, 2025)
This study discusses the Home Industry of Pasah Kripik Crafts in Babadan Village, Patianrowo District, Nganjuk, which is able to compete and excel in the market to this day. The Home Industry of Pasah Kripik Crafts has a marketing strategy to increase company revenue by prioritizing product quality. This study analyzes the marketing strategy implemented by the Home Industry of Pasah Kripik Crafts reviewed from the perspective of Sharia Marketing and the impact of the Home Industry of Pasah Kripik Crafts on increasing community income. The researcher used a qualitative method with interview, documentation, and observation data collection techniques. The results of the study showed that the marketing strategy of the Home Industry of Pasah Kripik Crafts using the sharia concept, namely theistic (Rabbaniyah), ethical (Akhlaqiyyah), realistic (Al-Waqi'iyyah), and humanities (Insniyyah) was able to increase company revenue. The conclusion of this study is that the Home Industry of Pasah Kripik Crafts business in Babadan Village, Patianrowo District, Nganjuk is able to compete in the market, and is able to increase the economy of community income.